Slug-expressing mouse prostate epithelial cells have increased stem cell potential - Kahounová, Zuzana; Remšík, Ján; Fedr, Radek; Bouchal, Jan; Mičková, Alena; Slabáková, Eva; Binó, Lucia; Hampl, Aleš; Souček, Karel (Stem cell research, 2020)
Deciphering the properties of adult stem cells is crucial for understanding of their role in healthy tissue and in cancer progression as well. Both stem cells and cancer stem cells have shown association with epithelial-to-mesenchymal transition (EMT) in various tissue types. Aiming to investigate the epithelial and mesenchymal phenotypic traits in adult mouse prostate, we sorted subpopulations of basal prostate stem cells (mPSCs) and assessed the expression levels of EMT regulators and markers with custom-designed gene expression array. The population of mPSCs defined by a Lin-/Sca-1+CD49fhi/Trop-2+ (LSC Trop-2+) surface phenotype was enriched in mesenchymal markers, especially EMT master regulator Slug, encoded by the Snai2 gene. To further dissect the role of Slug in mPSCs, we used transgenic Snai2tm1.1Wbg reporter mouse strain. Using this model, we confirmed the presence of mesenchymal traits and increase of organoid forming capacity in Slug+ population of mPSCs. The Slug+-derived organoids comprised all prostate epithelial cell types - basal, luminal, and neuroendocrine. Collectively, these data uncover the important role of Slug expression in the physiology of mouse prostate stem cells.
Keywords: Organoids; Male; epitelové buňky; Cell Line, Tumor; Epithelial-Mesenchymal Transition; Prostate; Epithelial Cells; Snai2/Slug; mužské pohlaví; prostata; Cell Movement; Stemness; Animals; zvířata; Snail Family Transcription Factors; Prostate stem cells; pohyb buněk; myši; Epithelial-to-mesenchymal transition; nádorové buněčné linie; Mice; rodina transkripčních faktorů Snail; epitelo-mezenchymální tranzice